A drug-responsive multicellular human spheroid model to recapitulate drug-induced pulmonary fibrosis. (1st July 2022) - Saygili, Ecem; Devamoglu, Utku; Goker-Bagca, Bakiye; Goksel, Ozlem; Biray-Avci, Cigir; Goksel, Tuncay; Yesil-Celiktas, Ozlem
Abstract: Associated with a high mortality rate, pulmonary fibrosis (PF) is the end stage of several interstitial lung diseases. Although many factors are linked to PF progression, initiation of the fibrotic process remains to be studied. Current research focused on generating new strategies to gain a better understanding of the underlying disease mechanism as the animal models remain insufficient to reflect human physiology. Herein, to account complex cellular interactions within the fibrotic tissue, a multicellular spheroid model where human bronchial epithelial cells incorporated with human lung fibroblasts was generated and treated with bleomycin (BLM) to emulate drug-induced PF. Recapitulating the epithelial-interstitial microenvironment, the findings successfully reflected the PF disease, where excessive alpha smooth muscle actin and collagen type I secretion were noted along with the morphological changes in response to BLM. Moreover, increased levels of fibrotic linked COL13A1, MMP2, WNT3 and decreased expression level of CDH1 provide evidence for the model reliability on fibrosis modelling. Subsequent administration of the Food and Drug Administration approved nintedanib and pirfenidone anti-fibrotic drugs proved the drug-responsiveness of the model.